2011
DOI: 10.1152/jn.00059.2011
|View full text |Cite
|
Sign up to set email alerts
|

Skilled throwers use physics to time ball release to the nearest millisecond

Abstract: Hore J, Watts S. Skilled throwers use physics to time ball release to the nearest millisecond. J Neurophysiol 106: 2024 -2033, 2011. First published July 20, 2011 doi:10.1152/jn.00059.2011.-Skilled throwers achieve accuracy in overarm throwing by releasing the ball on the handpath with a timing precision as low as 1 ms. It is generally believed that this remarkable ability results from a precisely timed command from the brain that opens the fingers. Alternatively, precise timing of ball release could result f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Conduction velocities of ϳ50 -70 m/s (Ingram et al 1987;Macefield et al 1989) and the ϳ30-to 50-cm distance between the shoulder and wrist muscles would yield goal-dependent activity at shoulder muscles 9 -20 ms prior to wrist muscles. Although this asynchrony may be slightly overestimated because we have not accounted for all physiological details (e.g., precise nerve innervation pattern; neuromuscular architecture), it is important to note that even small conduction delays could have functional consequences for the execution of goal-directed actions, which can require temporal precision on the order of 1-2 ms (Hore and Watts 2011). Our results indicate that the neural network that supports the long-latency stretch response may account for conduction delays by sending goal-dependent signals to distal muscles prior to proximal muscles-a process that apparently sacrifices the absolute response latency of muscles spanning proximal joints for a coordinated response across muscles spanning multiple joints.…”
Section: Discussionmentioning
confidence: 99%
“…Conduction velocities of ϳ50 -70 m/s (Ingram et al 1987;Macefield et al 1989) and the ϳ30-to 50-cm distance between the shoulder and wrist muscles would yield goal-dependent activity at shoulder muscles 9 -20 ms prior to wrist muscles. Although this asynchrony may be slightly overestimated because we have not accounted for all physiological details (e.g., precise nerve innervation pattern; neuromuscular architecture), it is important to note that even small conduction delays could have functional consequences for the execution of goal-directed actions, which can require temporal precision on the order of 1-2 ms (Hore and Watts 2011). Our results indicate that the neural network that supports the long-latency stretch response may account for conduction delays by sending goal-dependent signals to distal muscles prior to proximal muscles-a process that apparently sacrifices the absolute response latency of muscles spanning proximal joints for a coordinated response across muscles spanning multiple joints.…”
Section: Discussionmentioning
confidence: 99%
“…Hore and Watts [23] demonstrated that university baseball players demonstrated a series of successive throws with release timings as low as 1 ms. The results for our four experts that demonstrated the strategy of reducing Et seem to support the results of these previous studies [5], [6], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hore and Watts [23] demonstrated that university baseball players demonstrated a series of successive throws with release timings as low as 1 ms. The results for our four experts that demonstrated the strategy of reducing Et seem to support the results of these previous studies [5], [6], [23]. However, because of differences in the definitions of timing accuracy, our timing error results cannot simply be compared with those of the previous studies, which estimated the timing variability as the standard deviations with respect to a kinematic landmark.…”
Section: Discussionmentioning
confidence: 99%
“…Japan Science and Technology Agency, PRESTO, Saitama, Japan. 8 School of Life Science and Technology, Tokyo Institute of Technology, Kanagawa, Japan.…”
Section: Author Detailsmentioning
confidence: 99%
“…For example, for baseball pitchers, the release of the ball requires a very precise movement, with only añ 2 ms time window to pitch the ball into the strike zone. The palm muscles appear to play a key role in this movement [6][7][8][9][10] . Because the ball directly touches the palm muscles, sEMG recording from the palm muscles during an actual pitch is extremely difficult, and even the most recent recording modules cannot be utilized.…”
Section: Introductionmentioning
confidence: 99%